2003
DOI: 10.1039/b300466j
|View full text |Cite
|
Sign up to set email alerts
|

Conformational behavior of some hydroxamic acids

Abstract: The conformational preferences of a few hydroxamic acids are investigated by the density functional B3LYP/6-311++G**//B3LYP16-31G* and semiempirical AM1 and PM3 methods in this work. It is found that both semiempirical methods give satisfactory results in comparison with sophisticated DFT and ab initio calculations, except for the activation barriers, which are overestimated. Of the two semiempirical methods, while the PM3 method gives better results for relative stabilities, AM1 geometries are in slightly bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 33 publications
(26 reference statements)
1
30
2
Order By: Relevance
“…This step involves unexpected barrier of 9.86 kcal/mol via TS6. This barrier value is in reverse with previously reported results for formohydroxamic acid [22]. Judging from the transition barriers it seems that the S2-TS4-1E is the slowest reaction step and it is endothermic with an energy barrier equal to 43.09 kcal/mol.…”
Section: Energy Analysiscontrasting
confidence: 55%
“…This step involves unexpected barrier of 9.86 kcal/mol via TS6. This barrier value is in reverse with previously reported results for formohydroxamic acid [22]. Judging from the transition barriers it seems that the S2-TS4-1E is the slowest reaction step and it is endothermic with an energy barrier equal to 43.09 kcal/mol.…”
Section: Energy Analysiscontrasting
confidence: 55%
“…Low-quality calculations suggested that FHA exists preferentially as the 1E-keto isomer with OH bond in anti-orientation in the gas phase [21,25,28,32]. At the higher levels of theory, when more extended basis set and correlation energy were used, the 1Z-keto isomer with the OH bond involved in an intramolecular hydrogen bond, was predicted to be the most stable one.…”
Section: Introductionmentioning
confidence: 92%
“…A number of theoretical calculations were performed related to the structural analysis of FHA [21][22][23][24][25][26][27][28][29][30][31][32][33] and AHA [34][35][36][37][38][39]. Low-quality calculations suggested that FHA exists preferentially as the 1E-keto isomer with OH bond in anti-orientation in the gas phase [21,25,28,32].…”
Section: Introductionmentioning
confidence: 99%
“…[50] The conformational preferences of some hydroxamic acids have recently been investigated by density functional and empirical methods. [51] Figure 5. Tautomeric forms of hydroxamic acids…”
Section: Syntheses and Structuresmentioning
confidence: 98%